Treatment Outcomes of Clopidogrel in Patients With ACS and Diabetes Undergoing PCI-Analysis of Beijing Municipal Medical Insurance Database - Wang, Weihao; Wang, Xiaoxia; Zhang, Lina; Zhang, Jie; Man, Fuli; Pan, Qi; Guo, Lixin (Frontiers in Endocrinology, 2021)
Abstract Background and Aims Several clinical trials have proved the efficacy of clopidogrel treatment for patients with percutaneous coronary intervention. There are few large-scale studies to identify the mortality associated with different durations of treatment of clopidogrel in patients with diabetes and ACS undergoing PCI in the Chinese population. The objective of this analysis was to determine the efficacy of long-term clopidogrel therapy (≥12 months) versus short-term use (<12 months) in Chinese patients with diabetes after PCI. Methods and Results We used the Beijing Municipal Medical Insurance Database provided by the Beijing Municipal Medical Insurance Bureau. The Beijing Municipal Medical Insurance Database contained medical data of about 16 million people, including about 990,000 patients with diabetes and a history of taking antidiabetic medicines. Patients were divided into two groups, one group of 9,116 patients receiving consecutive clopidogrel for one year or more, and another group of 3290 patients receiving consecutive clopidogrel for less than one year. The primary outcomes of this analysis were the risk of all-cause death, myocardial infarction, and revascularization. In patients with diabetes after PCI, long-term clopidogrel treatment was associated with a reduced risk of all-cause death (HR, 0.57[95%CI, 0.49-0.67], P<0.0001), myocardial infarction (HR, 0.79[95%CI, 0.68-0.93], P=0.0035) and an increased risk of angina (HR, 1.18[95%CI, 1.10-1.27], P<0.0001]) and revascularization (HR, 1.07[95%CI, 1.01-1.13], P=0.02]). There was no significant difference in the prevalence of all-cause re-hospitalization, diabetes-related re-hospitalization, and cerebrovascular re-hospitalization. Conclusion The present study concluded that long-term dual antiplatelet therapy including clopidogrel and aspirin could decrease the risks of all-cause death, myocardial infarction. But it could increase the risks of angina and revascularization. Further studies should interpret the cause of this question.